2015
DOI: 10.1007/s11060-015-1793-2
|View full text |Cite
|
Sign up to set email alerts
|

BCNU wafer placement with temozolomide (TMZ) in the immediate postoperative period after tumor resection followed by radiation therapy with TMZ in patients with newly diagnosed high grade glioma: final results of a prospective, multi-institutional, phase II trial

Abstract: Temozolomide (TMZ) and BCNU have demonstrated anti-glioma synergism in preclinical models. We report final data from a prospective, multi-institutional study of BCNU wafers and early TMZ followed by radiation therapy with TMZ in patients with newly diagnosed malignant glioma. 65 patients were consented in 4 institutions, and 46 patients (43 GBM, 3 AA) were eligible for analysis. After resection and BCNU wafer placement, TMZ began on day four postoperatively. Radiation and TMZ (RT/TMZ) were then administered, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It has become the current standard chemotherapeutic drug in the treatment for glioma. However, the development of inherent or acquired TMZ resistance limits its clinical application, and the mechanisms of TMZ resistance are not fully understood . Thus, identification of new molecular targets is urgently required to fight against TMZ resistance in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…It has become the current standard chemotherapeutic drug in the treatment for glioma. However, the development of inherent or acquired TMZ resistance limits its clinical application, and the mechanisms of TMZ resistance are not fully understood . Thus, identification of new molecular targets is urgently required to fight against TMZ resistance in glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Burri et al included an immediate postoperative 5-day cycle of TMZ beginning on day 4 ± 1, dosed at 150–200 mg/m 2 per day [29]. Concurrent TMZ at 75 mg/m 2 then began at day 33 ± 1 with RT; after completion of concurrent treatment, adjuvant TMZ was begun and administered at 150–200 mg/m 2 per day for 5 days per 28-day cycle for up to 10 cycles or until progression or patient intolerance [29]. Because the Burri et al trial was a multisite phase II study, it was included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Only two of the trials in this systematic review reported MGMT analysis. Burri et al reported MGMT promoter methylation status for 22 of 43 patients with GBM (out of 46 patients total in the study) [29]. In the study by Noel et al, MGMT promoter methylation status was reported for all 65 patients: 24 patients were methylated, 27 patients were unmethylated, and 14 patients were not analyzed [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations